Gliotoxin Targets Nuclear NOTCH2 in Human Solid Tumor Derived Cell Lines In Vitro and Inhibits Melanoma Growth in Xenograft Mouse Model - Hubmann, Rainer; Sieghart, Wolfgang; Schnabl, Susanne; Araghi, Mohammad; Hilgarth, Martin; Reiter, Marlies; Demirtas, Dita; Valent, Peter; Zielinski, Christoph; Jäger, Ulrich; Shehata, Medhat (Frontiers in Pharmacology, 2017)
Deregulation of NOTCH2 signalling is implicated in a wide variety of human neoplasias. The current concept of targeting NOTCH is based on using gamma secretase inhibitors (GSI) to regulate the release of the active NOTCH intracellular domain. However, the clinical outcome of GSI remains unsatisfactory. Therefore we analysed human solid tumour derived cell lines for their nuclear NOTCH activity and evaluated the therapeutic potential of the NOTCH2 transactivation inhibitor gliotoxin in comparison to the representative GSI DAPT. Electrophoretic mobility shift assays (EMSA) were used as a surrogate method for the detection of NOTCH/CSL transcription factor complexes. The effect of gliotoxin on cell viability and its clinical relevance was evaluated in vitro and in a melanoma xenograft mouse model. Cell lines derived from melanoma (518A2), hepatocellular carcinoma (SNU398, HCC-3, Hep3B), and pancreas carcinoma (PANC1) express high amounts of nuclear NOTCH2. Gliotoxin efficiently induced apoptosis in these cell lines whereas the GSI DAPT was ineffective. The specificity of gliotoxin was demonstrated in the well differentiated nuclear NOTCH negative cell line Huh7, which was resistant to gliotoxin treatment in vitro. In xenotransplanted 518A2 melanomas, a single day dosing schedule of gliotoxin was well tolerated without any study limiting side effects. Gliotoxin significantly reduced the tumour volume in early (83mm3 vs 115mm3, p00.008) as well as in late stage (218mm3 vs 576mm3, p=0.005) tumour models. In conclusion, NOTCH2 appears to be a key target of gliotoxin in human neoplasias and gliotoxin deserves further evaluation as a potential therapeutic agent in cancer management.